Penerapan Good Corporate Governance Terhadap Kecurangan (FRAUD) Perbankan Syariah - Daulay, Wilda Efrilyati; Azhari, Farah Indah; Triningsih, Cindy; Nasution, Juliana (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2022)
The purpose of this study is to examine how Islamic banking fraud is combated by implementing GCG (Good Corporate Governance). Apart from analyzing financial ratios, another aspect that needs to be observed and evaluated is the implementation of Good Corporate Governance (GCG). The business management's adherence to the correct management system and all applicable legal regulations, including statutory regulations, government policies, Bank Indonesia legal instruments, and internal legal regulations, are inseparable from the application of good corporate governance principles. banking and is inseparable from banking managers' awareness of the following principles of good corporate governance: in banking management, transparency, accountability, responsibility, fairness, and independence. The consistent use of the standards of good corporate administration can lessen the gamble of misrepresentation as shown by the diminishing pattern of extortion cases. Sharia principles like honesty (shiddiq), community education (tabliq), trust (amanah), and professional management of management (fathanah) should also be applied in good corporate governance.